Lectotype designations, taxonomic notes and new synonymy in some species of the bee genus Centris Fabricius, 1804 described by William Henry Fox (Hymenoptera: Apidae) - Vivallo, Felipe (Zootaxa, 2019)
In this paper, the primary types of Centris described by the American doctor and naturalist William Henry Fox deposited at the Academy of Natural Sciences, Drexel University, Philadelphia and in the United States National Museum, Washington, United States were studied. To stabilize the application of some names, lectotypes were designated for C. atriventris Fox (= C. foxi Friese), C. cockerellii Fox, C. eisenii Fox, C. errans Fox, C. pallida Fox, C. subhyalina Fox (= C. lanosa Cresson), and C. xylocopoides Fox. This latter species is withdrawn from the synonymy of C. braccata Packard and subsequently revalidated. Centris foxi is removed from synonymy of C. atripes Mocsáry and revalidated, proposing this latter species as its new junior synonym. A taxonomic note on the primary type of C. marginata Fox (= C. caesalpiniae Cockerell) is also provided.